Eu empregada doméstica: narrativas, sentidos e significados na luta pela efetivação de direitos das trabalhadoras domésticas no Brasil - Almeida, Lyzyê Inácio (2019)
The present dissertation resulted in a qualitative and interdisciplinary research that selects narratives of lute by working directors of domestic enterprises, especially by black women who perform and perform this function as the case of Laudelina de Campos Mello. Besides this methodological inverse, were added to these narratives of fights an analysis gives initiative of creation gives page of Facebook: Eu Empregada Doméstica, which presents stories of domestic servants, constituting the data that were analyzed in search for their meanings. Therefore, revelations have been extracted from the virtual space of the internet, where the fanpage Eu Empregada Doméstica has its impact and diversification of two records of domestic workers, who expose their daily lives in the employers' house. These workers were stimulated by actions previous not virtual world such as those of Joyce Fernandes, also known as Preta Rara, who denounced offenses and prejudices suffered in environment of domestic work. Or I have studied the made it possible or scope of the central objective of the research, which is to be followed more closely with the fact that these are stories, more than any other day or day of work, but supplications for the realization of a more contextual objective than é a effectiveness of their fundamental rights. In this way, it is possible to confirm the hypothesis that, in a context that has been incorporated into a broadening of domestic workers' rights, at the present time, it can be ascertained an updated perpetuity of the escravagista past.